In Situ Fiber Optics Analysis of MicroparticlesofaPoorly Water Soluble Drug - Betty Philip, Dr (International Journal of Pharmaceutical & Biological Archive, 2014)
In Situ Fiber Optics Analysis of MicroparticlesofaPoorly Water Soluble Drug